(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study assessed beef and poultry consumption patterns in Ondo West’s urban households. The study’s goals were to examine the socioeconomic characteristics of these households, the frequency of beef and poultry consumption, and preferences for beef and poultry meat. A multi-stage sampling technique was used to select 100 respondents from five towns in Ondo West LGA. Data were collected using structured questionnaires and analyzed using descriptive statistics. According to the findings, 50% of the respondents were of equal gender, 58% were married, and 64% were between the ages of 21 and 40. Furthermore, 52% reported have a monthly income of #31,000 to #60,000. The study also revealed that households preferred beef and poultry meat, with mean ratings of 3.62 and 3.64, indicating a positive attitude towards both. Consumers rated beef as more affordable than chicken, with a mean score of 3.45. The survey indicated beef was the most desired meat, with the highest mean score of 3.74, indicating its widespread usage among households studied. This study found that beef is the most consumed and preferred meat in Ondo West. Efforts should focus on increasing beef production and raising awareness about the nutritional benefits of poultry to encourage its consumption.